Molecular phylogeny of Thoe Bell, 1836 (Crustacea, Brachyura, Majoidea) - Colavite, Jessica; Windsor, Amanda Marie; Moraes, Isabela Ribeiro Rocha [UNESP]; Mollemberg, Michelle [UNESP]; Lianos, Laira [UNESP]; Castilho, Antonio Leao [UNESP]; Santana, William (Soc Brasileira Carcinologia, 2022)
Thoe Bell, 1836 is amphi-American in distribution and includes small spider crabs with cryptic habits and rare records in the literature and carcinological collections. The taxonomy of the three recent and two fossil species currently known in the genus has been revised. A phylogenetic reconstruction conducted here based on the mitochondrial markers COI and 16S rRNA supports the monophyletic status of Thoe. The resulting phylogeny suggests a western Atlantic to eastern Pacific radiation of the genus.
Keywords: Decapoda; Eastern Pacific; Mithracidae; spider crab; taxonomy; Western Atlantic